Treatment of cosmetic effluent in different configurations of ceramic UF membrane based bioreactor: Toxicity evaluation of the untreated and treated wastewater using catfish (Heteropneustes fossilis). (March 2016) - Banerjee, Priya; Dey, Tanmoy kumar; Sarkar, Sandeep; Swarnakar, Snehasikta; Mukhopadhyay, Aniruddha; Ghosh, Sourja
Abstract: Extensive usage of pharmaceutical and personal care products (PPCPs) and their discharge through domestic sewage have been recently recognized as a new generation environmental concern which deserves more scientific attention over the classical environmental pollutants. The major issues of this type of effluent addressed in this study were its colour, triclosan and anionic surfactant (SDS) content. Samples of cosmetic effluent were collected from different beauty treatment salons and spas in and around Kolkata, India and treated in bioreactors containing a bacterial consortium isolated from activated sludge samples collected from a common effluent treatment plant. Members of the consortium were isolated and identified as Klebsiella sp., Pseudomonas sp., Salmonella sp. and Comamonas sp. The biotreated effluent was subjected to ultrafiltration (UF) involving indigenously prepared ceramic membranes in both side-stream and submerged mode. Analysis of the MBR treated effluent revealed 99.22%, 98.56% and 99.74% removal of colour, triclosan and surfactant respectively. Investigation of probable acute and chronic cyto-genotoxic potential of the untreated and treated effluents along with their possible participation in triggering oxidative stress was carried out with Heteropneustes fossilis (Bloch). Comet formation recorded in both liver and gill cells and micronucleus count in peripheral erythrocytes of individuals exposed to untreated effluent increased with duration of exposure and was significantly higher than those treated with UF permeates which in turn neared control levels. Results of this study revealed successful application of the isolated bacterial consortium in MBR process for efficient detoxification of cosmetic effluent thereby conferring the same suitable for discharge and/or reuse. Graphical abstract: Highlights: First detailed report of cosmetic pollution effects and its treatment using MBR. 99.04, 98.14 and 99.12% color, triclosan, surfactant removal by isolated bacteria. Efficient performance of indigenously prepared cost effective ceramic membranes. Toxicity assay suggested that treated permeate was biologically safe for discharge. UMBR proved an efficient, low-cost and convenient process for wastewater treatment.